The role of non-governmental organisations in social sustainability: The case of Maybank / Fatin Amirah Suhaimi - Fatin Amirah , Suhaimi (2021)
This study attempts to understand the roles of secondary stakeholders, namely the NGOs, in the dimensional perspective of social sustainability. It also investigates communication strategies evolved over the years by the NGOs in social sustainability and to the extent of which such communications are able to exert their influences on the banking industry in Malaysia. This is a case study concept and uses secondary data as a data collection. The qualitative content analysis is performed to validate a theoretical framework using data from Twitter and online news that is related to the subject of this study, which is the Malayan Banking Berhad (Maybank). Twitter and online news data, which focuses on social sustainability context from the year 2010 to 2018 are analysed, by using Braun and Clarke’s (2006) 6-step framework thematic analysis technique with the assistance of the Nvivo12 programme. The relationship with NGOs as a social actor through collaboration and partnership is considered to be potentially beneficial to the banking industry in implementing their sustainable strategies. The roles of NGOs as capacity builders, bridgers, initiators and advocators have been identified in the context of social sustainability within Maybank Berhad. The emerging roles of NGOs, namely as digital activists, have been revealed significantly with digital convergence of communication strategies in tackling social issues. The digital convergence significantly transforms media communication and the way NGOs communicate over the years, from stakeholder’s information and response to its involvement in implementing strategic activities. This study fills the gap in the literature by defining the roles of NGOs and their communication strategies in social sustainability through Twitter and online news, which are two major media platforms, in the context of social sustainability. This study provides valuable insight for the banking and other services industry, both the public and the private sector to strategize their stakeholder collaboration approach with NGOs and to plan their communication strategies in the context of social sustainability on an online media platform.